Marine Heat Waves Hazard 3D Maps and the Risk for Low Motility Organisms in a Warming Mediterranean Sea - Galli, Giovanni; Solidoro, Cosimo; Lovato, Tomas (Frontiers in Marine Science, 2017)
Frequency and severity of heat waves is expected to increase as a consequence of climate change with important impacts on human and ecosystems health. However, while many studies explored the projected occurrence of hot extremes on terrestrial systems, few studies dealt with marine systems, so that both the expected change in marine heat waves occurrence and the effects on marine organisms and ecosystems remain less understood and surprisingly poorly quantified. Here we: i) assess how much more frequent, severe, and depth-penetrating marine heat waves will be in the Mediterranean area in the next decades by post-processing the output of an ocean general circulation model; and ii) show that heat waves increase will impact on many species that live in shallow waters and have reduced motility, and related economic activities. This information is made available also as a dataset of temperature threshold exceedance indexes that can be used in combination with biological information to produce risk assessment maps for target species or biomes across the whole Mediterranean Sea. As case studies we compared projected heat waves occurrence with thermotolerance thresholds of low motility organisms. Results suggest a deepening of the survival horizon for red coral (Corallium rubrum, a commercially exploited benthic species already subjected to heat-related mass mortality events) and coralligenous reefs as well as a reduction of suitable farming sites for the mussel Mythilus galloprovincialis. In recent years Mediterranean circalittoral ecosystems (coralligenous) have been severely and repeatedly impacted by marine heat waves. Our results support that equally deleterious events are expected in the near future also for other ecologically important habitats (e.g. seagrass meadows) and aquaculture activities (bivalvae), and point at the need for mitigation strategies.